Robust Financial Contracting and the Role of Venture Capitalists. - Admati, Anat R; Pfleiderer, Paul (Journal of Finance, 1994)
The authors derive a role for inside investors, such as venture capitalists, in resolving various agency problems that arise in a multistage financial contracting problem. Absent an inside investor, the choice of securities is unlikely to reveal all private information and overinvestment may occur. An inside investor, however, always makes optimal investment decisions if and only if he holds a fixed-fraction contract, where he always receives a fixed fraction of the project's payoff and finances that same fraction of future investments. This contract also eliminates any incentives of the venture capitalist to misprice securities issued in later financing rounds.